Wayang Kancil Fairy Tale Training for Teachers and Parents of KB 'Aisyiyah Surya Melati Students to Increase Knowledge of Tolerance in Early Childhood - Tri Winarsih; Nur Fitri Mutmainah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Tolerance is respecting and accepting differences in opinions, culture, religion and other values. In an increasingly diverse society, character education becomes very important to create individuals who can live side by side peacefully. Unfortunately, the value of tolerance in Indonesia is starting to fade, and many cases of intolerance occur in various circles. The government, through the Ministry of Education, Culture, Research and Technology, has intensified character education programs at all levels of education, including early childhood education (PAUD). This community service activity aims to increase the knowledge and skills of teachers and parents of KB 'Aisyiyah Surya Melati students in forming children's character through storytelling activities using the Wayang Kancil media to instill the values of tolerance in early childhood. Through this training, it is hoped that it can form a tolerant character in children from an early age. The method used in implementation was socialization and training with a total of 25 participants consisting of teachers and parents of KB 'Aisyiyah Surya Melati students. The results of the activity showed a significant increase in understanding and storytelling skills for teachers and parents. Through these training activities, we succeeded in increasing the knowledge and skills of teachers and parents in storytelling by using the Wayang Kancil media to instill the values of tolerance in young children. It is hoped that this activity can support the formation of children's tolerant, intelligent and ethical character.